indonesia - Amanda, Nila; Hasbiah Ainun; Rokhimah (Institut Agama Islam Negeri Kendari, 2026)
Work readiness is a crucial factor in preparing university graduates to compete in the labor market. This study aimed to examine the contributions of work motivation and Field Experience Practice (PPL) to the work readiness of students at the Faculty of Sharia and Da’wah, IAIN Sorong, Class of 2022. Using a quantitative causal-associative approach, data were collected from 74 active students through a saturated sampling technique and analyzed using multiple linear regression in SPSS Version 32. The findings revealed that work motivation has a positive and significant effect on work readiness (t = 3.227; p = 0.002), while PPL also positively and significantly influences work readiness (t = 3.482; p < 0.001). Furthermore, both variables simultaneously have a significant effect on work readiness (F = 51.769; p < 0.001), explaining 58.2% of the variance in students’ work readiness. These results indicate that strengthening work motivation and optimizing field experience programs are essential strategies for enhancing graduates’ readiness, competence, and competitiveness in the labor market.